Polyhydroxyalkanoates Production By Cupriavidus Necator Mutants From Glucose By Innovative Fermentation Strategies - Biglari, Nazila (2020)
Polyhydroxyalkanoate (PHA) is synthesized intracellularly by many microorganisms and has potential as a biodegradable polymer. Due to the low productivity and yield, only few microorganisms have been cultivated at industrial scale to produce the PHA using natural and abundant carbon source. Cupriavidus necator wild strain H16 can assimilate some simple sugars and oils but does not utilize glucose. C. necator NSDG-GG and C. necator NSDG˗GGΔB1/pBPPccrMeJAc- emd mutants are new strains developed to produce PHA from glucose. The purpose of this study was to optimize the culture conditions to produce poly(3- hydroxybutyrate) [P(3HB)] and poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) [P(3HB-co-3HHx)] polymers by using these new mutants. Initially, appropriate ranges of nutrients concentration (urea and glucose) were determined to obtain the highest biomass and PHA by using the one-factor-at-a-time (OFAT) approach. Then, a response surface methodology (RSM) was applied to optimize the key variables ata- time to attain the optimal condition of biomass and PHA production in a multivariable system. The optimized medium compositions which improved the biomass and PHA production, were used to design fed-batch cultivation modes to scale-up the biomass and PHA production in a 5 L bioreactor. Subsequently, a filland- draw (F/D) fed-batch strategy was employed to understand the key parameters that impacted the total cell densities and PHA concentration in the increment and decrement fed-batch modes.